Partisan preferences and political institutions: explaining fiscal retrenchment in the European Union - Oliver Pamp (Free University Berlin, Jean Monnet Centre of Excellence, 2004)
Driven by the desire to fulfill the Maastricht fiscal criteria and pressed by mounting debt burdens that have accumulated over the past 30 years, a majority of EU-15 countries attempted to reduce their budget deficits during the 1990s. Yet, these nations have exhibited remarkable differences in their ability to pursue such retrenchment policies. This paper endeavours to illuminate the political and institutional factors that can help explain those differing degrees of fiscal retrenchment in European Union countries for the time period 1990-2001. Several variants of the partisan approach and the veto players framework are elucidated and applied to the question of budgetary consolidation. These elaborations yield four working hypotheses which are empirically tested using a time-series cross-section data set of 14 EU countries. The results lend support to the notion that a low number of insitutional veto players increases likelihood and extent of a budgetary retrenchment. Given these findings it is possible to draw some conclusions concerning the effectiveness and deficiencies of the Stability and Growth Pact.
Keywords: C23; D72; D78; H62; 330; deficits; fiscal adjustment; partisan theory; veto players; time-series cross-secton models